2017
DOI: 10.1130/g38938.1
|View full text |Cite
|
Sign up to set email alerts
|

East African weathering dynamics controlled by vegetation-climate feedbacks

Abstract: Tropical weathering processes hold important linkages to global biogeochemistry, as well as landscape evolution including in the East African rift valley. We disentangle the influences of climate change and terrestrial vegetation on chemical weathering intensity and erosion at Lake Malawi using a long sediment record. Fossil pollen, microcharcoal, particle size, and mineralogy data affirm that the types of allochthonous clays accumulating in deepwater within the lake is controlled by feedbacks between climate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Previous studies have shown that OC and SR accumulation are controlled by the complex interplay of primary productivity, dilution and preservation of OM, which are further influenced by a number of factors such as lake level fluctuations, changes in hinterland and basin slope angles and inorganic sediment and terrestrial OM input 3,6,7,[10][11][12][50][51][52][53][54] . Despite recent progress in understanding these processes (e.g., Bohacs et al 55 , Ellis et al 6 ), SR accumulation in rift-lake systems is particularly complex and therefore remains hard to generalize 3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that OC and SR accumulation are controlled by the complex interplay of primary productivity, dilution and preservation of OM, which are further influenced by a number of factors such as lake level fluctuations, changes in hinterland and basin slope angles and inorganic sediment and terrestrial OM input 3,6,7,[10][11][12][50][51][52][53][54] . Despite recent progress in understanding these processes (e.g., Bohacs et al 55 , Ellis et al 6 ), SR accumulation in rift-lake systems is particularly complex and therefore remains hard to generalize 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Organic carbon (OC) accumulation and development of petroleum source rocks (SR) are complex processes involving a number of interrelated factors, the relative importance of which are not fully understood 1 , 2 . Furthermore, many of the factors can be scale dependent 3 what makes direct comparison with studies dealing with surface sediments, representing shorter time spans or different settings convoluted 4 7 . Lacustrine rift basins are especially challenging in this regard due to localized and evolving topography through the active rifting phase, which typically cause profound changes in factors controlling organic matter (OM) production and preservation 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the evolution of Al/K ratios and other weathering proxies in sedimentary records is generally considered to reflect past fluctuations in alteration processes coupled with changing hydroclimate and vegetation patterns on continents (e.g. Schneider et al, 1997;Bayon et al, 2012;Ivory et al, 2017). At the Congo margin, the utility of Al/K for reconstructing past chemical weathering has been demonstrated using Hf isotopes, which represent another powerful indicator for silicate weathering intensity (Bayon et al, 2009(Bayon et al, , 2012.…”
Section: Past Weathering and Erosion Changes: Al/k Bit-index And Inimentioning
confidence: 99%
“…The bulk geochemistry of sediments in the EARS reflects their provenance and weathering, as well as their depositional, chemical and diagenetic histories, which result from a complex interplay between geological and climatological controls (WoldeGabriel et al ., ; Owen et al ., ). Weathering, for example, leads to loss of labile elements (Nesbitt & Young, ), but the weathering intensity might reflect either climate (Ivory et al ., ) or relative uplift and subsidence rates, which control exposure time to weathering.…”
Section: Introductionmentioning
confidence: 99%